(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the views of thinkers and their theoretical significance in correcting negative behavior of students. It is emphasized that the use of pedagogy and psychology in shaping the behavior of students is of great importance. The author analyzes the views of thinkers on the methods of education necessary for the personal development and social adaptation of the student.